Sustainability Reporting in Emerging Economies : Challenges and Opportunities for Accountants - Sukma Kusuma Dewa; Faradiva Wieke Prasasti; Diah Ayu Lestari (Harmoni Economics: International Journal of Economics and Accounting, 2024)
Sustainability reporting has gained prominence worldwide, but its adoption in emerging economies faces significant barriers due to regulatory, financial, and institutional challenges. This paper examines the current state of sustainability accounting practices in emerging markets, focusing on the alignment of corporate social responsibility (CSR) and environmental, social, and governance (ESG) disclosures. The study also investigates the role of accountants in promoting transparency and standardization in sustainability reporting. The research highlights key issues such as lack of infrastructure, limited regulatory frameworks, and the need for capacity building in emerging economies.